'It just didn't really happen': The lived space of entrepreneurial urbanism in Ørestad, Copenhagen. Issue 123 (July 2021) - Ösgård, Anton; Spierings, Bas
Highlights: LUDs risk resulting in residents struggling to develop place identity/attachment. Discourses associated with entrepreneurial urbanism can result in image-reality gaps. Ørestad, Copenhagen failed to become the cosmopolitan metropole it was intended to. Image-reality gaps resulted in experiences of transition and opposition in Ørestad. Abstract: This paper explores the lived space of entrepreneurial urbanism in Ørestad, a 1990s mega-project still under development on the edge of Copenhagen. Drawing upon in-depth interviews, interactive map-making and critical discourse analysis, it shows that imaginaries of urban competition, place branding and cosmopolitanism have only superficially been internalized by residents as part of their lived space in Ørestad, even revealing contradictory everyday practices and experiences. Rather than the cosmopolitan metropole and connected city space it was conceived to become, the district is experienced as a disconnected housing satellite without much street life, as a stepping stone to something better by reducing home to exchange value, and as an area with a community based in opposition. A sense of place identity and place attachment does exist for many Ørestaders but it is born out of 'do-it-yourself mentality' and reaction to a sense of ephemerality. The lived space of entrepreneurial urbanism in Ørestad can only partly be understood by what the district is, but much more by what it is not – i.e. by what it lacks from the perspective of its residents.